2x^2-3x-2=0

First let us find the zeros of the equation:

(2x+1)(x-2)=0

==> x= -1/2 and x=2

Or alpha=-1/2 and beta=2

Now we need to find the equation whose roots are:

2alpha+beta or 2(-1/2)+2=1

and 2beta+alpha OR 2(2)-1/2 = 7/2

Then the factors are:

(x-1)(x-7/2)=0

x^2-(9/2)x+7/2=0

Multiply by 2:

2x^2+9x+7=0

Then the...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

2x^2-3x-2=0

First let us find the zeros of the equation:

(2x+1)(x-2)=0

==> x= -1/2 and x=2

Or alpha=-1/2 and beta=2

Now we need to find the equation whose roots are:

2alpha+beta or 2(-1/2)+2=1

and 2beta+alpha OR 2(2)-1/2 = 7/2

Then the factors are:

(x-1)(x-7/2)=0

x^2-(9/2)x+7/2=0

Multiply by 2:

2x^2+9x+7=0

Then the function is:

f(x) = 2x^2+9x+7